1977
DOI: 10.3758/bf03198716
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of time intervals marked by brief acoustic pulses of various intensities and spectra

Abstract: Experienced observers were asked to identify, in a four-level 2AFC situation, the longer of two unfilled time intervals, each of which was marked by a pair of 20-msec acoustic pulses. When all the markers were identical, high-level (86-dB SPL) bursts of coherently gated sinusoids or bursts of band-limited Gaussian noise, a change in the spectrum of the markers generally did not affect performance. On the other hand, for I-kHz tone-burst markers, intensity decreases below 25 dB SL were accompanied by sizable de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
113
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 25 publications
15
113
1
Order By: Relevance
“…Except in those cases where a subject's phoneme boundary fell near an anchor (see Figure 2 for the boundaries), the ordering of the anchors is quite straightforward: the shorter the voice onset time of the anchor, the better the performance. These results are quite similar to those obtained in a study of the discriminability of a nonspeech timing feature (Divenyi & Danner, 1977 ences: discrimination improves most near the continuum ends. Figure 1 indicates that performance on the anchors at the ends of the continuum (0-and 81-msec VaT) improved most; the other curves are generally flat.…”
Section: Methodssupporting
confidence: 80%
“…Except in those cases where a subject's phoneme boundary fell near an anchor (see Figure 2 for the boundaries), the ordering of the anchors is quite straightforward: the shorter the voice onset time of the anchor, the better the performance. These results are quite similar to those obtained in a study of the discriminability of a nonspeech timing feature (Divenyi & Danner, 1977 ences: discrimination improves most near the continuum ends. Figure 1 indicates that performance on the anchors at the ends of the continuum (0-and 81-msec VaT) improved most; the other curves are generally flat.…”
Section: Methodssupporting
confidence: 80%
“…Figure 3 shows that beyond an approximately twooctave separation between the CF of high and low NBNs, there is no further increase in the difficulty of holding on to a single stream. In a review of this paper, Pierre Divenyi (personal communication,December 1998) pointed out that similar observations have been made for the discrimination of unfilled intervals between two tones of different frequencies (Divenyi & Danner, 1977) and for the detection of gaps between narrow-band noise-burst markers (Formby, Barker, Abbey, & Raney, 1993). The similarity suggests to Divenyi that all these observations may be looking at the same process: frequency integration in temporal processing.…”
Section: Discussionmentioning
confidence: 76%
“…541 There seems to exist a general agreement on the fact that when an observer is asked to discriminate between intervals of short duration, his performance is little affected by such stimulus characteristics as intensity, frequency, and bandwidth (Allan, 1979). More specifically, if the discrimination is performed on empty intervals marked by short auditory pulses, numerous studies have shown that, for intervals longer than 100 msec, performance is not sensitive to variations in marker intensity (Abel, 1972;Carbotte & Kristofferson, 1973;Divenyi& Danner, 1977;Penner, 1976), frequency or spectrum (Divenyi & Danner, 1977;Divenyi & Sachs, 1978), and duration (Abel, 1972;Carbotte & Kristofferson, 1973;Penner, 1976). Moreover, within the range of 0-100 msec, Nilsson (1969) and Oostenbrug, Horst, and Kniper (1978) have shown the performance to be relatively insensitive to changes in the energy of light pulse markers.…”
mentioning
confidence: 99%
“…In general, discrimination models consider that the encoding of temporal extent is performed by a central timekeeper common to visual and auditory modalities (Allan, 1979). Most current models do assume that duration information is obtained through the accumulation, over the extent of the interval, of pulses originating in some central source (Abel, 1972;Creelman, 1962;Divenyi & Danner, 1977;Kinchla, 1972;Thomas & Brown, 1974;Treisman, 1963). Although some models (Creelman, 1962;Divenyi & Danner, 1977) have formally defined parameters representing nontemporal stimulus variables, their theoretical importance has remained very minor in view of the empirical evidence.…”
mentioning
confidence: 99%